Formation features of reflexion in future faculties of music art - Варганич, Г. О.; Хоменко, З. В. (Scientific notes of the pedagogical department, 2019)
The article reveals the components of the system of formation of the pedagogical reflexion of the future specialist of musical art, in detail the procedural-technological features and the leading methods and methods that are aimed at actualizing the potential opportunities of music education students in the process of preparing for practical pedagogical activity. Reflexion is the comprehension and experience of the individual in the study of his own activities, awareness of himself in the context of social life, in the context of the way of existence. Under reflexion they understand self-examination, introspection of their own psyche, analysis of life’s values, ideological settings, and others like that. Reflection acts as an instrument of self-knowledge. Reflexion of the future teacher of musical art is considered as a set of functional components: motivational-value, emotional-empathy, productive-creative. The motivational-value component is represented by the steady interest of higher education graduates in the future profession and the development of the motivational sphere, which forms the installation of conductor-choral activity. The emotional-empathic component consists in reflexive analysis and sensory perception of the future musical art teachers of the best samples of choral music. The development of the emotional and sensory sphere of the applicant of higher education is the basis of his professional attitude in general and the process of formation of reflexion. The productive and creative components of the focus on the spiritual and creative self-realization of future professionals in musical art. The future teacher of musical art is important to understand and adequately perceive oneself, to determine the prospects of self-development, to use their own emotional, spiritual and moral reserves. This reflexion blocks activities based on old patterns and opens up new ways for thinking and action. The professional reflexion of the teacher is a process of awareness, understanding and rethinking the problems of professional activity. Formation of reflexion from future specialists in musical art from setting the goal to determining the component structure, principles, functions and pedagogical conditions can be represented as a holistic pedagogical model.